Gestão da qualidade aplicada no processo de poda de árvores em uma distribuidora de energia - KOGA, Flávio Hiroshi Pecoraro (2018)
The requirement to deliver high quality and uninterrupted electrical energy to customers increases more and more as time goes by. The prevailing mode of medium voltage distribution network (DN) in the state of Maranhão is the conventional air network, which type is the most vulnerable, since its conductors do not have any protection, being exposed to the elements in the weather. A major problem for energy utilities is the interaction between trees and DN drivers. The vegetation causes interruption in the supply of electric energy when it comes in contact with the energized naked conductor, negatively impacting the collective indicators of continuity of energy distribution. Tree in the network was the cause that generated the most deenergizations in the state of Maranhão in the years 2016 and 2017. In this context, improving the pruning process of trees of Companhia Energética do Maranhão (CEMAR) is a sine qua non for the evolution of collective indicators of continuity of the state's energy distribution. The PDCA quality tool and the Study of Times, Movements and Methods were applied in order to improve the efficiency of CEMAR's pruning service. In addition, the correct method of execution of the pruning service was verified, referring to NBR 16246-1 and the good practices adopted by other energy distributors. Training was given to the pruning teams and guidelines were established to be followed. As Maranhão is a state of rich flora, a table with all the possible types of prunings to be applied in the maintenance of the CEMAR’s DN was established, according to the nature of each species of vegetation. A method of naming and identifying pruning types has been developed through a three-digit coding. As a result of this work, it was possible to reduce 43.76% of the total time of the AML pruning service, in addition to also reducing the team's average downtime. Mowers became aware of the correct way to perform pruning and better contribute to the achievement of results.